Urban Living Labs: how to enable inclusive transdisciplinary research? - Pia Laborgne (BMC, 2021)
Abstract The Urban Living Lab (ULL) approach has the potential to create enabling environments for social learning and to be a successful arena for innovative local collaboration in knowledge co-creation and experimentation in the context of research and practice in sustainability transitions. Nevertheless, complex issues such as the urban Food-Water-Energy (FWE) Nexus present a challenge to the realization of such ULL, especially regarding their inclusiveness. We present ULL as a frame for a local knowledge co-creation and participation approach based on the project "Creating Interfaces - Building capacity for integrated governance at the Food-Water-Energy-nexus in cities on the water". This project aims at making FWE Nexus linkages better understandable to the stakeholders (citizens and associations, city government, science, businesses), and to facilitate cooperation and knowledge exchange among them. This paper focuses on and discusses inclusiveness as a key aspect and challenge of ULLs and on what literature and our experiences in this regard suggest for the advancement of the concept of ULL towards ULL 2.0. These findings often also relate to framing transdisciplinary research in a wider sense.